Alternative Models for the Percentage Distribution of Progress Levels in Research Projects - Dios-Castillo, Christian Abraham (2024)
Introduction. There is a need to standardize the percentage distribution of research project progress levels. The research problem is: How can a percentage distribution of research project progress levels be designed, considering qualitative criteria? The general objective is to develop alternative models of percentage distribution of research project progress levels while considering qualitative criteria. Methodology. The study employed a descriptive-projective level of methodological development. The unit of analysis comprised descriptive, correlational, or explanatory research projects conducted by university faculty, with a total population of 126 projects. The research design was descriptive-longitudinal, utilizing documentary analysis as the data collection and analysis technique. A documentary analysis form was used as the instrument, and data processing was conducted quantitatively by calculating the percentage progress levels for each project. Results. Three models were developed for determining the progress levels of research projects, incorporating different criteria of percentage distribution, which can be considered for measuring results. Discussion. There is a logical relationship between the fundamental components of a strategy, enabling its effective development and impact on the results achieved. Measuring the effectiveness of a strategy requires integrating the achievement of specific objectives into the general objective. Therefore, it is important to consider a hierarchy of indicators to understand each phase’s contribution to achieving each specific objective; this includes determining the percentage of contribution to the project’s progress.